Degradasi Zat Warna Methyl Violet dengan Katalis ZnO/Ag Menggunakan Metode Fotosonolisis - Rahma Sari; Hary Sanjaya; Yohandri Yohandri; Ali Amran; Ananda Putra (Jurnal Periodic Jurusan Kimia UNP, 2022)
Abstract – the photosonolysis method was used for the degradation of methyl violet in the sample solution using a ZnO doping Ag catalyst. This study aims to determine the effect of radiation time and the addition of Ag doping on ZnO catalyst on the degradation of Methyl violet. UV-Vis spectrophotometer was used to calculate the absorbance concentration of methyl violet before and after degradation while UV-DRS was used to measure the band gap value. The results showed that the highest percentage of Methyl violet degradation was 93.51% at 120 minutes using ZnO without doping. The highest degradation of methyl violet was at 90.50% using a 10% ZnO/Ag catalyst. the band gap obtained from the measurement of ZnO/Ag is 3.26%.Keywords: degradasi, Methyl Violet, ZnO/Ag, Photosonolysis, Band gap